Change in Corporate Debt Levels in South Africa from 1994 to 2016 - van der Westhuizen, Kyla (Department of Finance and Tax, 2021)
This paper investigated the change in corporate debt levels in South Africa from 1994 to 2016. Included is an analysis of factors that companies take into consideration when determining the company's capital structure. This study used data from companies, largely from the mining sector, within sectors listed on the Johannesburg Stock Exchange (JSE), including chemicals, general industries, oil and gas. Four different leverage measures were used to determine the change in capital structure for the period under review, as well as six of the most commonly used determinants of capital structure. A high-level interpretation of the results reflected the following; a slight but relatively consistent increase in the use of debt relative to equity over the period for both the total sample and the mining sector. An increase in the use of long- relative to short term debt was also found, as well as a convergence between the use of current and non-current liabilities. Results from the analysis of the capital structure determinants varied, with some showing statistical significance. Asset tangibility was positively correlated to debt, while profitability and growth had a negative relationship. The relationship between company size, tax and cost of debt and leverage was varied.